Analysis Qualitative Branding Based Entrepreneurship : Its Influence to Brand Positioning and Startup Performance in the Digital World - Anggendari, Tursinah; Nurhasanah, Sri Utami (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the impact of entrepreneurship-based branding on brand positioning and startup performance in the digital era. The study highlights the significance of a brand-centric approach, emphasizing continuous brand identity development through customer interaction to achieve sustainable competitive advantages. Key factors such as risk-taking, business situation analysis, organizational structure, and market orientation play crucial roles in shaping effective branding strategies. The findings suggest that strategic brand positioning, planning, and value creation enhance brand positioning and startup performance. This research provides valuable insights for practitioners in branding and entrepreneurship, offering practical guidance for improving startup performance through brand-centric strategies. However, the study is limited by its reliance on existing literature and the lack of direct empirical analysis. Future research should involve empirical studies to validate these findings in practical contexts and explore the influence of external factors on entrepreneurial branding effectiveness.